If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 7y = 2x + 7 + 6y Reorder the terms: 5 + 7y = 7 + 2x + 6y Solving 5 + 7y = 7 + 2x + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 5 + 7y + -6y = 7 + 2x + 6y + -6y Combine like terms: 7y + -6y = 1y 5 + 1y = 7 + 2x + 6y + -6y Combine like terms: 6y + -6y = 0 5 + 1y = 7 + 2x + 0 5 + 1y = 7 + 2x Add '-5' to each side of the equation. 5 + -5 + 1y = 7 + -5 + 2x Combine like terms: 5 + -5 = 0 0 + 1y = 7 + -5 + 2x 1y = 7 + -5 + 2x Combine like terms: 7 + -5 = 2 1y = 2 + 2x Divide each side by '1'. y = 2 + 2x Simplifying y = 2 + 2x
| 16x+12=8x+41 | | 6x=3x+3 | | 9x+6=-57 | | r^3-3r+2=0 | | y=3(1)-10 | | 3x-10=2x-5 | | P(x)=x^3+7x^2+4x | | m^6-16m^3+64=0 | | 6x+3=6(4)+3 | | .50(6-y)=y | | -10.2x=71.4 | | 4x^2-33x+41=-9x+6 | | 6t=-46 | | 5x-9=4(x-3) | | 5p=-15 | | -9(2b+3)+(19b-3)=0 | | 7y^2-8y+15-11y^2-8y+6= | | a^2+8a=9 | | x=-11 | | -(3x+5)+1-4(x-2)+5x-2=0 | | x^2-2x+4=8x-4 | | t^2-10t-24=0 | | x^2+12x+6=0 | | 4x+3(2x-8)=8x-40 | | 4.5x-3.8y+6.9x-0.2y= | | 2s+7=10s-7 | | 27+2x+3=5x | | 2s+7=10-7 | | X^2-2x+4=-8x-4 | | 5x+63=7(x-9) | | n-7=13 | | x+2/3= |